2007
DOI: 10.1103/physrevb.76.144102
|View full text |Cite
|
Sign up to set email alerts
|

Electronic topological transition in zinc under pressure: An x-ray absorption spectroscopy study

Abstract: Zinc metal has been studied at high pressure using x-ray absorption spectroscopy. In order to investigate the role of the different degrees of hydrostaticity on the occurrence of structural anomalies following the electronic topological transition, two pressure transmitting media have been used. Results show that the electronic topological transition, if it exists, does not induce an anomaly in the local environment of compressed Zn as a function of hydrostatic pressure and any anomaly must be related to a los… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 33 publications
(31 reference statements)
0
5
0
Order By: Relevance
“…Interestingly, the fitting results reveal an abrupt increase for the σ 2 of the Bi–Se1 (Te1) and Bi–Se2 (Te2) bonds at 4.8 (2.5) GPa in concert with the above local structure distortion. In EXAFS, the Debye–Waller factor measures the width of the bond‐distance distribution g ( r ) around the photoabsorber, which takes into account both thermal and structural disorders linked to the local vibrational dynamics and to the local structural distortions, respectively . The thermal part usually would be suppressed by compression and could not lead to an abrupt change of the EXAFS Debye–Waller factor.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, the fitting results reveal an abrupt increase for the σ 2 of the Bi–Se1 (Te1) and Bi–Se2 (Te2) bonds at 4.8 (2.5) GPa in concert with the above local structure distortion. In EXAFS, the Debye–Waller factor measures the width of the bond‐distance distribution g ( r ) around the photoabsorber, which takes into account both thermal and structural disorders linked to the local vibrational dynamics and to the local structural distortions, respectively . The thermal part usually would be suppressed by compression and could not lead to an abrupt change of the EXAFS Debye–Waller factor.…”
Section: Resultsmentioning
confidence: 99%
“…Even for a simple metallic Zn foil, the conventional EXAFS tting underestimates the coordination numbers by up to 50%. 13,70,71 By our NN approach, in turn, the analysis of such disordered structures can be done easily. RDFs extracted by NN from the Cu K-edge and Zn K-edge EXAFS data (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This was triggered by a Mössbauer spectroscopy study which suggested that an electronic topological transition occurs in Zn at 6.6 GPa [25]. This work was followed by a series of studies using different techniques [19,[26][27][28][29][30][31][32][33][34]. All these studies were carried out at RT (or below it) and were focused on compressibility, the supposed anomaly of c/a, and the proposed electronic topological transition.…”
Section: Introductionmentioning
confidence: 99%